PRICE TRANSMISSION DYNAMICS BETWEEN ADRs AND THEIR UNDERLYING FOREIGN SECURITY: THE CASE OF BANCO DE COLOMBIA S.A.- BANCOLOMBIA (Artículo publicado en inglés) (Estudios Gerenciales, 2005)
This paper analyzes the dynamics of the American Depositary Receipt (ADR) of a Colombian bank (Bancolombia) in relation to its pricing factors (underlying (preferred)shares price, exchange rate and the US market index). The aim is to test if there is a long-term relation among these variables that would imply predictability. One cointegrating relation is found allowing the use of a vector error correction model to examine the transmission of shocks to the underlying prices, the exchange rate, and the US market index. The main finding of this paper is that in the short run, the underlying share price seems to adjust after changes in the ADR price, pointing to the fact that the NYSE (trading market for the ADR) leads the Colombian market.  However, in the long run, both, the underlying share price and the ADR price, adjust to changes in one another.